Micro-scaled topographies direct differentiation of human epidermal stem cells. (15th January 2019) - Zijl, Sebastiaan; Vasilevich, Aliaksei S.; Viswanathan, Priyalakshmi; Helling, Ayelen Luna; Beijer, Nick R.M.; Walko, Gernot; Chiappini, Ciro; de Boer, Jan; Watt, Fiona M.
Graphical abstract: Abstract: Human epidermal stem cells initiate terminal differentiation when spreading is restricted on ECM-coated micropatterned islands, soft hydrogels or hydrogel-nanoparticle composites with high nanoparticle spacing. The effect of substrate topography, however, is incompletely understood. To explore this, primary human keratinocytes enriched for stem cells were seeded on a topographical library with over 2000 different topographies in the micrometre range. Twenty-four hours later the proportion of cells expressing the differentiation marker transglutaminase-1 was determined by high content imaging. As predicted, topographies that prevented spreading promoted differentiation. However, we also identified topographies that supported differentiation of highly spread cells. Topographies supporting differentiation of spread cells were more irregular than those supporting differentiation of round cells. Low topography coverage promoted differentiation of spread cells, whereas high coverage promoted differentiation of round cells. Based on these observations we fabricated a topography in 6-well plate format that supported differentiation of spread cells, enabling us to examine cell responses at higher resolution. We found that differentiated spread cells did not assemble significant numbers of hemidesmosomes, focal adhesions, adherens junctions, desmosomes or tight junctions. They did, however, organise the actin cytoskeleton in response to the topographies. Rho kinase inhibition and blebbistatin treatment blocked the differentiation of spread cells, whereas SRF inhibition did not. These observations suggest a potential role for actin polymerization and actomyosin contraction in the topography-induced differentiation of spread cells. Statement of Significance: The epidermis is the outer covering of the skin. It is formed by layers of cells called keratinocytes. The basal cell layer contains stem cells, which divide to replace cells in the outermost layers that are lost through a process known as differentiation. In this manuscript we have developed surfaces that promote the differentiation of epidermal stem cells in order to understand the signals that control differentiation. The experimental tools we have developed have the potential to help us to devise new treatments that control diseases such as psoriasis and eczema in which epidermal stem cell proliferation and differentiation are disturbed.